Beispiel Nr: 05
$ \text{Gegeben:}\\\text{Diagonale} \qquad d \qquad [m] \\ \text{Breite} \qquad a \qquad [m] \\ \\ \text{Gesucht:} \\\text{Länge} \qquad b \qquad [m] \\ \\ b = \sqrt{d^{2} -a^{2} }\\ \textbf{Gegeben:} \\ d=25m \qquad a=24m \qquad \\ \\ \textbf{Rechnung:} \\ b = \sqrt{d^{2} -a^{2} } \\ d=25m\\ b=7m\\ b = \sqrt{(25m)^{2} -(24m)^{2} }\\\\b=7m \\ \small \begin{array}{|l|} \hline d=\\ \hline 25 m \\ \hline 250 dm \\ \hline 2,5\cdot 10^{3} cm \\ \hline 2,5\cdot 10^{4} mm \\ \hline 2,5\cdot 10^{7} \mu m \\ \hline 0,025 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline a=\\ \hline 24 m \\ \hline 240 dm \\ \hline 2,4\cdot 10^{3} cm \\ \hline 2,4\cdot 10^{4} mm \\ \hline 2,4\cdot 10^{7} \mu m \\ \hline 0,024 km \\ \hline \end{array}\\ \small \begin{array}{|l|} \hline b=\\ \hline 7 m \\ \hline 70 dm \\ \hline 700 cm \\ \hline 7\cdot 10^{3} mm \\ \hline 7\cdot 10^{6} \mu m \\ \hline 0,007 km \\ \hline \end{array}\\$